Prenatal and Postnatal Clinical Spectrum of a Mosaic Small Supernumerary Marker Chromosome 22 - Tug, Esra; Karaoguz, Meral Yirmibes; Ergun, Mehmet Ali (International Journal of Pediatrics and Child Health, 2019)
An amniocentesis was performed because of the advanced maternal age at 18 weeks of gestation, and cytogenetic analyses revelaed a de novo mosaic small supernumerary marker chromosome (sSMC), as parental karotypes were normal. Fluorescence in situ hybridization (FISH) analyses with chromosome specific whole chromosome painting, locus, and alphoid satellite DNA probes were ended with the diagnosis of mosaic sSMC of chromosome 22. The result was explained to the family and genetic counselling was given together with the absence of fetal ultrasound findings. The baby was delivered at term by caesarean section. The female neonate with mosaic sSMC did not show any apparent dysmorphic features at birth. No growth and psychomotor retardation were observed at her natal period follow-up. At one year age, she had some mild dysmorphic findings such as high frontal hairline, frontal bossing, thin eyebrows, hypertelorism, flattened tip of nose and prominent philtrum. The reason of the absence of major abnormalities could be related with the presence of heterochromatin region of chromosome 22 rather than the gene rich parts. Finally, this report emphasizes the importance of acting in an analytical algorithm based on chromosomal origin, parental lineage, size and mosaic or non-mosaic status of sSMCs in the prenatal diagnosis, and using FISH technique and postnatal confirmation of the sSMC.